(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
mathematical description of the thermal conductivities λ of frozen and non-frozen wood has been introduced in an own non-linear mathematical model of the logs’ freezing process. For the numerical solution of the model a software program has been prepared in the calculation environment of Visual Fortran Professional. With the help of the program, the 2D non-stationary distribution of the temperature and the change of λ in the longitudinal section of poplar logs with diameter of 240 mm and length of 480 mm during their 50 h freezing in a freezer at about –30 oC have been calculated. The change of λ in the radial and longitudinal directions of the wood on both surfaces and in the center of the subjected to freezing logs during the freezing process has been calculated, visualized and analyzed.